NATIONAL-AESTHETIC IDEAS OF INTERPRETATION OF THE IMAGE OF THE HERO IN SCHOOL TEXTBOOKS ON UKRAINIAN LITERATURE 1991-1999 - Йовенко, Лариса (Modern engineering and innovative technologies, 2023)
The article examines the tendencies of the interpretation of the image of the hero in school textbooks on Ukrainian literature from 1991 to 1999 for a wider application in the educational process of the concept of the hero as an example for imitation, a m